2004
DOI: 10.1111/j.1475-6773.2004.00235.x
|View full text |Cite
|
Sign up to set email alerts
|

Updated Variable‐Radius Measures of Hospital Competition

Abstract: Objective. To calculate variable‐radius measures of hospital market size and create measures of competition for hospitals' markets. Data Sources. Discharge abstracts from the 1997 State Inpatient Databases of the Healthcare Cost and Utilization Project (HCUP) linked with the American Hospital Association (AHA) Annual Survey, Area Resource File (ARF), InterStudy Regional Market Analysis database, and Medicare's Prospective Payment System Impact Files. Study Design. Hospital radii capturing 75 and 90 percent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
3
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 4 publications
0
55
3
1
Order By: Relevance
“…However, we note that other research has found that 75% of discharges among acute care urban hospitals took place within a 10-mile radius. 12 Because hospital utilization data were not available by patient address, we aggregated population and hospital *Reports and statistics for individual cities and suburban areas are available at www.downstate.edu/ healthdata. This report series was the successor to an earlier grant from Robert Wood Johnson Foundation to examine health and socio-economic trends of the nation_s 100 largest cities, from 1980 to 1990. resource and utilization data across all cities and across all suburbs.…”
Section: Methodsmentioning
confidence: 99%
“…However, we note that other research has found that 75% of discharges among acute care urban hospitals took place within a 10-mile radius. 12 Because hospital utilization data were not available by patient address, we aggregated population and hospital *Reports and statistics for individual cities and suburban areas are available at www.downstate.edu/ healthdata. This report series was the successor to an earlier grant from Robert Wood Johnson Foundation to examine health and socio-economic trends of the nation_s 100 largest cities, from 1980 to 1990. resource and utilization data across all cities and across all suburbs.…”
Section: Methodsmentioning
confidence: 99%
“…We included four categories of covariates expected to relate to QI scope, hospital quality indicators, or both: market characteristics, hospital characteristics, accreditation and quality standards, and length of QI experience. In terms of market characteristics, we included three competition variables: a variable-radius Herfindal index of market concentration, defined as the sum of the squared market shares of the hospitals within a radius capturing 75 percent of a hospital's patient admissions in 1997 (Gresenz, Rogowski, and Escarce 2004); the self-reported number of other hospitals with which the hospital directly competes for patients on either an inpatient or outpatient basis; and the self-reported intensity of competition for patients among hospitals in the market, measured on a seven-point scale that ranged from (1) ''not at all intense'' to (7) ''highly intense''. We also included two managed care variables: managed care penetration, defined as the percentage of the total insured population in a county enrolled in a private risk, Medicare risk, or Medicaid risk insurance product in 1997; and self-reported percentage of patients for which hospital is paid on a capitated, negotiated per case rate, or discounted basis (excluding Medicare and Medicaid).…”
Section: Methodsmentioning
confidence: 99%
“…In estimating the impact of hospital competition on cost, we found that estimates from MSA based measures were consistently smaller in absolute value than county and HSA based measures, which in turn were smaller in absolute value than fix radius, variable radius, and patient flow based measures. MSA and county based measures are relatively easy for researchers to obtain, and updated variable radius measures are available to researchers from Gresenz et al (2004). Using these three measures would give researchers a sense of the range into which the point estimates they wish to obtain would fall.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due, in part, to the complexity of these approaches and the significant resources to obtain and to process the data. 21 Research continues to be published in renown general economics, health economics, and policy-oriented journals using the traditional approaches: Burdorf et al (2004), Gresenz et al (2004), Bamezai et al (2003), Carey (2003), Cuellar and Gertler (2003), Dranove and Lindrooth (2003), Sloan et al (2003), Duggan (2002), Gaskin et al (2002), Gift et al (2002), Greenberg and Goldberg (2002), Meltzer et al (2002), Sari (2002), and Santerre and Adams (2002).…”
Section: Hospital Competition Measuresmentioning
confidence: 97%
See 1 more Smart Citation